Synthesis and Physico-chemical Properties of Some Complexes of Tetradentate Macrocycles with Cd, Hg and Pb - Parihar, D.S. (Asian Journal of Chemistry, 2010)
The reaction of 3,6-diaza-1,8-diaminooctane with α-diketones viz., 2,3-butanedione, 2,3-pentanedione, 3,4-hexanedione or benzil in the presence of metal salts of Cd(II), Hg(II) and Pb(II) affords complexes of the type [MLX]X (M = Cd(II); X = NO3, M = Pb; X = ClO4) and [MLX2] (M = Cd(II), Hg(II); X = Cl). Elemental analyses, molar conductivity, molecular weight determination and spectra (IR and 1H NMR) have been used to characterize the structure of the isolated solid complexes. These studies suggest the coordination number five for Cd(II) and Pb(II) and six for Cd(II) and Hg(II).